Instituições residenciais para pessoas com deficiência intelectual: um programa educacional para promover qualidade no atendimento - Boueri, Iasmin Zanchi (Universidade Federal de São Carlos, 2014)
The aims of the current research were to characterize the residential institutions for intellectually disabled persons in the State of São Paulo (Brazil) and elaborate, implement and evaluate the efficacy of an Educational Program to Professionals working with young and adults with Intellectual Disabilities (PEP-DI). In order to improve the organization it was decided to divide the research in two studies. In the Study 1 the Institutions were characterized through the description of the activities and strategies used in the daily practices of the professionals working in it. It was chosen 10 Brazilian Residential Institutions with 113 participants, being 14 administrative persons, 49 professionals on the technical team and 50 persons living or working in the neighborhood of these Institutions. The participants answered three different semistructured surveys, one for each group of professionals and another for the neighborhood. The goals of the applied instruments were to verify historical aspects, operations and institutional practices. The researcher visited on the spot all the Institution for data acquisition. The results show that the creation of the Institution, in general, occurred through social demands and solicitations of the municipal offices for social assistance, however the maintenance is occurs by mean of philanthropic actions. Regarding the Institutional Practices is related to the health care, hygiene and alimentation. The aims of Study 2 were to elaborate, implement and evaluate the efficacy of an educational program, the PEP-DI; verify the behavioral changing related to the professionals repertory and intellectually disabled residents proportionate by applying the training program on the Institutional Environment. It was made an educational program, the PEP-DI, adapted to the reality of the studied institution. The participants were three professionals and 4 intellectually disable individuals of an Institution. The multiple probe design with subjects and with behaviors was chosen to verify the effects of the intervention amongst the participants. The event‟s registration protocol of was used to evaluate the entry repertory and the behavioral changes of the individuals before, during and after implementing the training program. The results show the participants modified significantly their professional repertory, once the residents presented better performance on their daily activities. The study discuss the current aspects faced by the Institutions and what changes must be done to proportionate more favorable environments, improvement on the life quality and social insertion of this population.
Keywords: Programação de ensino; Formação em serviço; Deficiência mental; Análise do comportamento; Programa de formação; Currículo funcional natural; Instituição residencial; Special education; Intellectual disability; Training program; Natural functional curriculum; Residential institution; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL